2016
DOI: 10.1186/s12916-016-0706-3
|View full text |Cite
|
Sign up to set email alerts
|

Maternal urinary metabolic signatures of fetal growth and associated clinical and environmental factors in the INMA study

Abstract: BackgroundMaternal metabolism during pregnancy is a major determinant of the intra-uterine environment and fetal outcomes. Herein, we characterize the maternal urinary metabolome throughout pregnancy to identify maternal metabolic signatures of fetal growth in two subcohorts and explain potential sources of variation in metabolic profiles based on lifestyle and clinical data.MethodsWe used 1H nuclear magnetic resonance (NMR) spectroscopy to characterize maternal urine samples collected in the INMA birth cohort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
59
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(63 citation statements)
references
References 45 publications
(50 reference statements)
3
59
0
1
Order By: Relevance
“…Few existing studies have investigated associations between maternal pregnancy metabolites and newborn size [9,10] and none have examined maternal metabolite profiles post glucose load or evaluated the relationship between maternal metabolites and newborn adiposity or cord C-peptide. A Spanish cohort of 800 mother-newborn pairs related maternal urinary metabolites during pregnancy with fetal and newborn size and similarly found that maternal urinary BCAAs, alanine, steroid hormones and choline were associated with greater intrauterine fetal growth and birthweight [9]. In a Polish cohort, mothers with lower lipid metabolites and higher adipocyte fatty acid-binding protein at 12-14 weeks of gestation had infants with larger birthweights, hypothesised to be due to greater mother-fetus transport of lipids [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few existing studies have investigated associations between maternal pregnancy metabolites and newborn size [9,10] and none have examined maternal metabolite profiles post glucose load or evaluated the relationship between maternal metabolites and newborn adiposity or cord C-peptide. A Spanish cohort of 800 mother-newborn pairs related maternal urinary metabolites during pregnancy with fetal and newborn size and similarly found that maternal urinary BCAAs, alanine, steroid hormones and choline were associated with greater intrauterine fetal growth and birthweight [9]. In a Polish cohort, mothers with lower lipid metabolites and higher adipocyte fatty acid-binding protein at 12-14 weeks of gestation had infants with larger birthweights, hypothesised to be due to greater mother-fetus transport of lipids [10].…”
Section: Discussionmentioning
confidence: 99%
“…In adults, branched-chain amino acids (BCAAs), aromatic amino acids (AAAs), short-chain acylcarnitines (C2, C6, C8; see ESM Table 1 for acylcarnitine nomenclature) and the carnitine ester of 3-hydroxybutyrate (acylcarnitine C4-OH) have all been associated with insulin resistance, higher HbA 1c and/or postprandial glucose levels [5][6][7][8]. However, the impact of the maternal metabolome on the developing fetus, as evidenced by newborn outcomes, is largely unknown and understudied [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, metabolomics analyses of cord blood may improve assessment of neonatal metabolic status beyond current knowledge of the implications of newborn size, and possibly may enhance assessment of future metabolic disease risk. To date, the literature includes only a few case-control studies comparing cord blood metabolite profiles of SGA (15) low birthweight (16), and very low birthweight (1719) newborn vs. their AGA or normal birthweight counterparts, as well as a few studies exploring associations of maternal urinary metabolites and with fetal growth restriction (20, 21). In general, these analyses revealed associations of low birthweight and poor fetal growth with alterations in amino acid and lipid metabolites (15, 16, 18, 19) indicative of impaired nutrient transfer to the fetus during development, as well as compounds on energy and polyamine metabolism pathways (17) that are upregulated during period of rapid cell turnover.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately a third of the retained exposome studies had a prospective longitudinal design (n = 30, 37%), of which 26 were based on nine large population-based cohorts; the rest four longitudinal studies were relatively small in size, including between 6 and 378 subjects [46][47][48][49]. Out of the 26 studies, eleven were published as part of the Human Early-Life Exposome (HELIX) project using data from six European birth cohorts ( [50][51][52][53][54][55][56]), and among these studies, four belonged to the Spanish INMA (INfancia y Medio Ambiente) [57][58][59][60][61]. Four studies (of the 26) were published as part of the Avon Longitudinal Study of Parents and Children (ALSPAC), a 20-year population-based cohort designed to determine the influence of environmental (physical and psychological) and genetic factors on the health status and development of the offspring.…”
Section: Description Of the Selected Articlesmentioning
confidence: 99%